The nursing: ethical-deontological aspects. - Cipressa, Salvatore (Medicina e Morale, 2003)
Technical-scientific tools and a suitable ethical-cultural education are necessary to qualify the health care services and to maintain a good level of professionalism of the health professionals. These factors make a reference to a Christian anthropology, that we can define person-centered perspective. It is requested to have an integral vision of man and his vocation that is not alone natural, but also eternal. In the article - according to this anthropological model - the Author shows delineates some attitudes and moral behaviours that characterise the nursing and traces the identity and the professional figure of the nurse. It follows that the nurse would live with humility and correctness its profession, contribute to humanise the health care, consider the patient a person to love; he loves the life and he sets to service of it, he is undertaken in a permanent education and he collaborates with the rest of the health care professionals. He is the Good Samaritan of our days, that stays close to the wounded man, doing him his neighbour in charity (cf. Lc 10, 29-37). In his professional relationship, the nurse is called to establish with the sick person a relationship of true, skilled and therapeutic help. Such a relationship constitutes the essence of the nursing and it is a particular relationship of ethical nature, that we can define a "meeting between a trust and a conscience". A trust of a man marked by suffering and illness and therefore a needy man, which entrusts to the "coscience" of another man that burdens himself with necessity of the patient and goes toward him to assist him, to take care of him, to recover him. For the christian nurse, the heart of the perfect exercise of nursing is Jesus Christ, who is the ethical-deontological model of reference to testify charity, and that has in the care of the sick his peculiar expression. Practicing his profession with science and conscience, the nurse expresses and testifies the charity of Christ.